Association Between Breastfeeding Initiation and Duration and Autism Spectrum Disorder in Preschool Children Enrolled in the Study to Explore Early Development. Issue 5 (9th March 2019) - Soke, Gnakub N.; Maenner, Matthew; Windham, Gayle; Moody, Eric; Kaczaniuk, Jamie; DiGuiseppi, Carolyn; Schieve, Laura A.
Abstract : Studies report inconsistent findings on the relationship between ASD and breastfeeding. We explored associations between ASD and breastfeeding initiation (yes/no) and duration (months categorized in tertiles) in the Study to Explore Early Development, a community‐based case–control study in six sites in the Unites States. We adjusted for various child and mother demographic and pregnancy factors. Breastfeeding initiation was reported in 85.7% of mothers of children with ASD and 90.6% of mothers of controls. After adjustment, we found no significant difference in breastfeeding initiation (adjusted odds‐ratio [aOR]: 0.88 and 95% confidence interval (CI) 0.60–1.28). However, mothers of children with ASD were less likely to report duration of breastfeeding in the high (≥12 months) versus low tertile (<6 months) (aOR and 95% CI: 0.61 [0.45–0.84]) or the middle (6–<12 months) versus low tertile (0.72: 0.54–0.98). The association of ASD and breastfeeding duration was slightly attenuated when the presence of the broader autism phenotype (BAP) in the mother was accounted for, but still remained for the highest tertile. This association does not appear to be totally explained by maternal BAP. We were unable to distinguish whether the difference in duration was due to difficulties breastfeeding children who later develop ASD, other factors not adjusted in our study, or greater ASD risk resulting from shorter breastfeeding duration. Longitudinal studies that compare reasons why mothers stop breastfeeding between ASD and controls and establish a temporal relation between ASD and breastfeeding are needed. Future studies should also evaluate interactions between ASD risk genes and breastfeeding. Autism Research 2019, 12: 816–829 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: In this study, we compared breastfeeding practices between mothers of children with and without autism spectrum disorder (ASD). We found that the percentage of mothers who started breastfeeding was similar between the two groups, but mothers of children with ASD breastfed for a shorter amount of time compared to mothers of children without ASD. Future studies are needed to evaluate the reasons why the duration of breastfeeding was shorter for mothers of children with ASD compared to those without ASD.